Clinical Features in Children With Kawasaki Disease Shock Syndrome: A Systematic Review and Meta-Analysis - Zheng, Zhimin; Huang, Yanzhi; Wang, Zhiyi; Tang, Jia; Chen, Xiaoqian; Li, Ying; Li, Meng; Zang, Chengye; Wang, Yibo; Wang, Liwu; Ma, Yingwei; Sun, Liwei (Frontiers in Cardiovascular Medicine, 2021)
Objective: This study aimed to identify the clinical features of Kawasaki disease shock syndrome (KDSS) in children. Methods: The case-control studies of KDSS and KD children up until April 30, 2021 were searched in multiple databases. The qualified research were retrieved by manually reviewing the references. Review Manager 5.3 software was used for statistical analysis. Results: The results showed that there was no significant difference in the incidence of male and female in children with KDSS. Children with KDSS compared with non-shocked KD, there were significant difference in age, duration of fever, white blood cell (WBC) count, percentage of neutrophils (NEUT%), platelet count (PLT), c-reactive protein level (CRP), alanine transaminase concentration (ALT), aspartate transaminase concentration (AST), albumin concentration (ALB), sodium concentration (Na), ejection fraction, and length of hospitalization as well as the incidence of coronary artery dilation, coronary artery aneurysm, left ventricular dysfunction, mitral regurgitation, pericardial effusion, initial diagnosis of KD, intravenous immunoglobulin (IVIG) resistance and receiving second dose of IVIG, vasoactive drugs, hormones, and albumin. In contrast, there was no difference in the hemoglobin concentration, erythrocyte sedimentation rate, and the incidence of conjunctival injection, oropharyngeal change, polymorphous rash, extremity change, and incomplete KD. Conclusion: Current evidence suggested that the children with KDSS had more severe indicators of inflammation and more cardiac abnormalities. These patients were resistant to immunoglobulin treatment and required extra anti-inflammatory treatment. Systematic Review Registration: PROSPERO registration number CRD42021241207.